Structure and functions of talking book mobile applications: a comparative study of Google Play Books, Audible, LibriVox, Storytel and Loyal Books - Bhardwaj, Raj Kumar; K.R., Abhilash (Performance measurement and metrics, 2024)
PurposeTalking book mobile applications have introduced the concept of reading through listening. Though conventional reading methods are preferable, talking book mobile applications have the advantage that they treat every user equally. The purpose of this paper is to compare the five popular talking book mobile applications namely Google Play Books, Audible, LibriVox, Storytel and Loyal Books.Design/methodology/approachThis research compares and evaluates features and functionalities of five different talking book mobile applications using a checklist method. A structured checklist is prepared to compare the five popular talking book mobile applications comprising 261 dichotomous questions divided into 13 categories.FindingsAfter evaluating the features, an attempt was made to rate the selected applications. According to the evaluation, Audible application performed better than others. This study about the features and functions of talking book mobile applications considered a total number of 261 features from the selected five mobile applications. Audible is ranked first with 182 (69.7%) features and is rated “Above average”; Storytel (68.2%) is second with 178 features, also rated “Above average”; Google Play Books ranked third with 161 (61.7%) features, rated “Average”; LibriVox ranked fourth with 151 (57.9%) features and is rated “Below average”. Fifth is Loyal Books with 130 (49.8%) features, rated “Below average”.Research limitations/implicationsThe study covers only five talking book mobile applications. The checklist used in the study is generic covering limited features. Further, the perceptions of users were also not included while comparing the talking book mobile applications. The study does not comprehend whether the talking book mobile applications fulfil the information needs of the users.Practical implicationsUsers can use the findings of the study in choosing the suitable talking book mobile application suitable to their requirements. Instructors of information literacy programmes can use the checklist to train the users in using talking book mobile applications that can accelerate the usage of these mobile applications.Originality/valueThe study identifies the features that should be available in a model talking book mobile application. Features of the talking book mobile applications were evaluated after preparing the detailed checklist. Features were divided into 13 different categories. The checklist used in the study is original and the first of its kind. The findings of the study can be used by developers of talking book mobile applications to improve their functionalities.